In vitro characterization of representative clinical South African Staphylococcus aureus isolates from various clonal lineages. Issue 4 (26th June 2014) - Oosthuysen, W. F.; Orth, H.; Lombard, C.; Sinha, B.; Wasserman, E.
Abstract Data concerning the virulence and pathogenesis of South African strains of Staphylococcus aureus are limited. We investigated host–pathogen interactions of randomly selected clinical S. aureus isolates representing various clones. We characterized the ability of isolates to adhere to fibronectin, fibrinogen, collagens IV and VI, to invade host cells and to induce cell death in vitro. We analysed the possible association of these results with characteristics such as methicillin resistance, Panton–Valentine leucocidin (PVL) positivity and clonality. The S. aureus isolates displayed diversity in their abilities to adhere to various human ligands. All isolates were highly invasive except for ST121. PVL‐negative isolates were significantly more invasive than the PVL‐positive isolates (p 0.004). Isolates of CC5, CC30 and CC121 were non‐cytotoxic, whereas isolates of CC22, CC8, CC15, CC45 and CC88 were very cytotoxic. No statistical association was identified between cell death and methicillin resistance, bacterial PVL status, clonality or patient HIV status. The vast majority of isolates were invasive and induced significant cell death. PVL‐negative isolates were more invasive than PVL‐positive isolates, while methicillin‐resistant isolates were not found to be more invasive or cytotoxic than methicillin‐susceptible isolates.